Self-cleaning dry adhesives - WANG RUOMIAO; XIE TAO (2010)
A shape memory polymer microfiber material coupled to a base portion and coated with a dry adhesive in which the tips of the microfibers may be modified to achieve superhydrophobicity. The resultant surface of the material may be altered between to an adhesive state from a superhydrophobic state as the shape memory polymer transforms from its permanent shape to a temporary shape. The shape memorypolymer microfiber material may be reversibly coupled to one or more substrates when in the adhesive state and uncoupled when in the superhydrophobic state.